Identifying saturated-unsaturated permeable properties by optimization of multi-objective nonlinear problem using fuzzy theory - Ohno, K. (Mie Univ., Tsu (Japan). Faculty of Bioresources); Kondo, T (Transactions of The Japanese Society of Irrigation, Drainage and Reclamation Engineering, 1991)
When earth structures, which retain water, are constructed, it is difficult to grasp the permeablity of the earth structures. The method, which identifies the permeable properties in saturated-unsaturated zone, has been developed by the fuzzy theory. Observed data are the heads of water. Identified parameters are coefficients of permeability in the saturated zone and permeable properties in the unsaturated zone. The reasons why the fuzzy theory must be used are that the observed data are thought to have not only stochastic sources of error but also many fuzzy ones and that the available information (i. e., engineering judgment) can be utilized besides the observed data. The comparison between calculated heads of water, which are calculated using the identified permeable properties and experimental ones, are in good agreement. The identified permeable properties have a reasonable character of seepage. So, the method developed here is thought to have validity. Much good information is needed to identify the permeable properties correctly. Usually, a big number of observed data can not be utilized. All identifying methods have this defectiveness. However, the identifying method developed here can use the available information besides the observed data. So, the method developed here is thought to have contributed to identifying the permeable properties.